Rapid and effective response of the R222Q SCN5A to quinidine treatment in a patient with Purkinje-related ventricular arrhythmia and familial dilated cardiomyopathy: a case report - Joanna Zakrzewska-Koperska; Maria Franaszczyk; Zofia Bilińska; Grażyna Truszkowska; Małgorzata Karczmarz; Łukasz Szumowski; Tomasz Zieliński; Rafał Płoski; Maria Bilińska (BMC, 2018)
Abstract Background Mutations of the SCN5A gene are reported in 2-4% of patients with dilated cardiomyopathy (DCM). In such cases, DCM is associated with different rhythm disturbances such as the multifocal ectopic Purkinje-related premature contractions and atrial fibrillation. Arrhythmia often occurs at a young age and is the first symptom of heart disease. Case presentation We present the case of 55-year old male with a 30-year history of heart failure (HF) in the course of familial DCM and complex ventricular tachyarrhythmias, which constituted 50-80% of the whole rhythm. The patient was qualified for heart transplantation because of the increasing symptoms of HF. We revealed the heterozygotic R222Q mutation in SCN5A by means of whole exome sequencing. After the quinidine treatment, a rapid and significant reduction of ventricular tachyarrhythmias and an improvement in the myocardial function were observed and this effect remained constant in the 2.5-year follow-up. This effect was observed even in the presence of concomitant coronary artery disease. Conclusions Patients with familial DCM and Purkinje-related ventricular arrhythmias should be offered genetic screening. The quinidine treatment for the SCN5A R222Q mutation can be life saving for patients.